L’homme (angut), le fils (irniq) et la lumière (qau): Ou le cercle du pouvoir masculin chez les Inuit de l’Arctique central - D’Anglure, Bernard Saladin (Anthropologica, 2022)
The study of some ideological productions of an Inuit group of Central Arctic demonstrates the primordial importance of the man/woman relationship. The study also places more value on the reproduction of life (procreation) than on the production of the material conditions of existence. Indeed, the process of procreation is the locus where the other social relations are articulated in a vast symbolic production. It is there that myths, rites, and social conducts establish the first social inequality: between men and women. The coercion thatsocial rules exert on women neutralizes their biological superiority in procreation and gives preeminence to men who, through shamanism in particular, hold a quasi-monopoly on knowledge (visionary capacity of the shaman), speech (esoteric shamanistic language) and social reproduction (capacity to act upon the invisible causes of reality). Women are thus confined to the domestic space where, instruments of their own alienation, they provide men with sons in the darkness of a warm home.